A combined 32‐channel receive‐loops/8‐channel transmit‐dipoles coil array for whole‐brain MR imaging at 7T - Clément, Jérémie; Gruetter, Rolf; Ipek, Özlem (Magnetic resonance in medicine, 2019)
Purpose Multichannel receive arrays provide high SNR and parallel‐imaging capabilities, while transmit‐only dipole arrays have been shown to achieve a large coverage of the whole‐brain including the cerebellum. The aim of this study was to develop and characterize the performances of a 32‐channel receive‐only loop array combined with an 8‐channel dipole coil array at 7T for the first time. Methods The 8Tx‐dipoles/32Rx‐loops coil array was characterized by the SNR, g‐factors, noise correlation matrix, accelerated image quality, and B1+ maps, and compared with a commercial 1Tx‐birdcage/32Rx‐loops array. Simulated and measured B1+ maps were shown for the 8Tx‐dipoles/32Rx‐loops coil array and compared with the 8Tx/Rx dipole array. Results The in‐house built 32‐channel receive coil demonstrated a large longitudinal coverage of the brain, particularly the upper neck area. G‐factors and accelerated MR acquisitions demonstrated robust performances up to R = 4 in 2D, and R = 8 (4 × 2) in 3D. A 83% increase in SNR was measured over the cerebellum with the in‐house built 8Tx/32Rx coil array compared to the commercial 1Tx/32Rx, while similar performances were obtained in the cerebral cortex. Conclusions The combined 32‐channel receive/8‐channel transmit coil array demonstrated high transmit‐receive performances compared to the commercial receive array at 7T, notably in the cerebellum. We conclude that in combination with parallel transmit capabilities, this coil is particularly suitable for whole‐brain MR studies at 7T.